2010
DOI: 10.1152/japplphysiol.00645.2010
|View full text |Cite
|
Sign up to set email alerts
|

Vortex formation time-to-left ventricular early rapid filling relation: model-based prediction with echocardiographic validation

Abstract: During early rapid filling, blood aspirated by the left ventricle (LV) generates an asymmetric toroidal vortex whose development has been quantified using vortex formation time (VFT), a dimensionless index defined by the length-to-diameter ratio of the aspirated (equivalent cylindrical) fluid column. Since LV wall motion generates the atrioventricular pressure gradient resulting in the early transmitral flow (Doppler E-wave) and associated vortex formation, we hypothesized that the causal relation between VFT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 38 publications
1
23
0
1
Order By: Relevance
“…Using the vortex boundary delineation provided by LCS in combination with particle tracing 6 , other quantitative measures such as fluid entrainment 24 may be computed. Recent studies have also suggested that vortex formation is linked to the load, stiffness and relaxation of the LV during rapid filling in humans 9 , and to LV pressure drop and the movement of the mitral annulus in heart-like phantoms 15,16 .…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Using the vortex boundary delineation provided by LCS in combination with particle tracing 6 , other quantitative measures such as fluid entrainment 24 may be computed. Recent studies have also suggested that vortex formation is linked to the load, stiffness and relaxation of the LV during rapid filling in humans 9 , and to LV pressure drop and the movement of the mitral annulus in heart-like phantoms 15,16 .…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…4D Flow CMR has enabled the characterization of the instantaneous time-evolution of 3D vortex ring flow within the LV over the complete diastole [44]. Formation of vortex ring flow has been suggested to help efficient MV closure and diastolic filling, minimize kinetic energy loss and prevent thrombus formation [1, 54, 64, 65]. Vortex flow patterns can change due to age, gender, blood pressure, ventricular geometry and mitral/atrioventricular valve abnormalities [45, 66].…”
Section: Applicationsmentioning
confidence: 99%
“…In a two dimensional (2D) four-chamber view a 3D vortex ring appears as a counter-rotating vortex pair, one distal to the anterior MV leaflet and another distal to the posterior leaflet. Such vortex formation may help in efficient MV closure [5], efficient diastolic filling, minimizing kinetic energy loss [4,6] and preventing thrombus formation [7]. An altered (early filling) vortex formation have been shown to develop in patients with diastolic dysfunction and dilated ischemic cardiomyopathy, suggesting a relation between abnormal vortex formation and LV dysfunction [7,8].…”
Section: Introductionmentioning
confidence: 99%